Uncovering implicit life values in Taxi Driver season 1: a semiotic analysis of moral messages through Roland Barthes’ framework - Dewi, Ria Sukma; Rizky Lutviana (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
The Korean drama Taxi Driver Season 1 presents a compelling narrative that combines intense action with emotional depth, tackling pressing social issues such as crime, revenge, and systemic injustice. This study applies Roland Barthes’ semiotic theory to analyze the embedded moral messages in episodes 3 and 4 of the series. Using a qualitative descriptive approach, the research focuses on interpreting signs, symbols, and cultural myths to uncover implicit life values conveyed through the story line and visual elements. Findings reveal that the drama makes extensive use of symbolic representations—most notably, the taxi as a metaphor for justice and a vehicle for vigilante retribution. These symbols reflect widespread societal disillusionment with the justice system’s inadequacies, particularly in safeguarding marginalized individuals and holding perpetrators accountable. The drama critiques institutional corruption and explores the ethical tension surrounding extrajudicial actions taken in the pursuit of justice. Despite its thematic emphasis on revenge, Taxi Driver ultimately conveys a deeper moral message that advocates for ethical restraint and lawful responses to injustice. The narrative encourages viewers to critically reflect on the societal structures that enable injustice and the moral consequences of bypassing those structures in pursuit of personal or collective retribution. In conclusion, Taxi Driver Season 1 functions not only as entertainment but also as a cultural text that invites ethical introspection and a reevaluation of personal and societal values in the face of moral and legal dilemmas.